As alterações da LINDB e a ponderação dos atos administrativos = The changes to the Statute of Introduction to the Rules of Brazilian Law (LINDB) and the balancing of administrative acts - Martins, Ricardo Marcondes (2020)
- DOI: 10.21056/aec.v20i79.1139